Manned spaceflight Log II-2006-2012 - Shayler, David J. (Springer Praxis Books, 2013)
April 12, 1961 "Attention! This is Radio Moscow speaking...The world's first satellite spaceship, Vostock, with a man aboard, was put into orbit round the Earth." Soviet Union cosmonaut Yuri A. Gagarin becomes the first person to fly in space, completing one orbit in 108 minutes. April 5, 2001 As NASA prepares to fly the final Shuttle missions to the International Space Station, Russia launches Soyuz TMA 21 (code-named 'Yuri Gagarin') with the 28th ISS Expedition crew aboard, celebrating 50 years of manned spaceflight. Meanwhile, in China, preparations continue for launching the nation's first Space Station (called Tiangong 1 - or Heavenly Palace 1) later in the year. The sixth decade of manned spaceflight orbital operations has truly began. At this point in the history of human space exploration, it is timely to review the first five decades of adventure and look forward to the next decade and what it might bring. Several notable anniversaries celebrated in 2011 make it the right time to reflect and pay homage before we move forward once more. As well as the 50th anniversary of Gagarin's Vostok flight, April 2011 also saw the 30th anniversary of the first Space Shuttle flight. Three months later, that program came to a close after its 135th mission and the completion of the majority of ISS assembly and outfitting. April also marked the 40th anniversary of the world's first orbital station, Salyut. The new Springer Manned Spaceflight Log II continues the story from 2006 up to the summer of 2012, with over 40 new entries, expanded tables and new photographs, some in color. Also featured are: - Details of over 40 recent missions which completed the International Space Station, serviced the Hubble Space Telescope for the final time, and commenced Chinese manned space station operations; - A summary of techniques and achievements across 50 years of human spaceflight operations; - A review of the next steps in human spaceflight, the birth of commercial operations, and plans for the next 20 years. This book complements the range of manned spaceflight books from Springer-Praxis.